WebSphere and .NET interoperability using Web services - Swithinbank, Peter (IBM redbooks., 2005)
IBM and Microsoft are strong supporters of the Web Services Interoperability Organization's (WS-I) efforts to make building solutions using software from different suppliers a reality. In this IBM Redbooks publication, we take a practical look at building a solution with IBM WebSphere and Microsoft .Net components using Web services that are compliant with the WS-I organization's Basic Profile. This book is aimed at customers who want to know how far the reality of Web services has caught up with the hype; it is for customers who want a book to help them decide whether Web services are right for them now. The book provides an introduction to SOAP, WSDL and the rest of the Web services concepts. It provides a review of the many Web service specifications. Which ones are most important to building a practical solution? We use a scenario based on work IBM has been doing with the insurance industry to demonstrate how to design a service-based solution and then implement it using the latest programming tools from IBM and Microsoft. Based on our experience, we identify areas where extra effort up front will be rewarded with an easier implementation. Please note that the additional material referenced in the text is not available from IBM.